APPLICATION OF HOLISTIC MARKETING IN THE FORMULATION OF A BUSINESS CONCEPT OF AGRICULTURAL PRODUCERS FROM SOUTH SERBIA - Dašić, Toma; Mihić, Svetlana; Šmelcerović, Miodrag (Economics of Agriculture, 2022)
The purpose of this paper is to analyze business concept of agricultural producers in Serbia and to show the necessity to define a new concept based on a holistic marketing approach. The components of holistic marketing are viewed from the standpoint of small scale fresh food producers in Serbia as economic entities. Analysis of current business situation, position of Serbian agricultural producers in agri-food supply chain and problems which they are facing are defined. Results of the analysis show the existing business orientation of producers and reveal their views regarding future business orientation. A presented solution to overcome the existing problems includes modernization of business by using combination of holistic marketing elements to create business concept which will provide conditions for improving competitiveness of agricultural producers. The conclusion has indicated the necessity of a new marketing approach for small scale producers in order to meet the challenges of modern business.